CORPORATE IMAGE MEDIATION BETWEEN TRUST AND MANAGERIAL CAPABILITIES TOWARD CUSTOMER SATISFACTION (Empirical Study of the Customer of Familie Hotel in Metro City) - Ngaliman Ngaliman (Derivatif : Jurnal Manajemen, 2018)
This research is motivated by the importance of customer satisfaction measurement using trust variable and managerial capability through company image. The research method used is explanatory survey and primary data. The sampling technique used questionnaire with likert scale to 150 respondents in Hotel Familie 2 Metro. Testing instrument requirements used include test validity and reliability test. Testing instrument analysis include lilifores normality test, homogeneity, linearity and regression significance. The tool used to test is the Structural Equation Model (SEM) and use the Linear Structural Relationship (LISREL) program which is a statistical program package for the structural equation model. Based on the findings of the research, it is known that trust does not affect the company image, managerial ability has a positive effect on the company's image, trust does not affect customer satisfaction, managerial ability has a positive direct effect to customer satisfaction, and corporate image has a positive effect on customer satisfaction. Keywords: trust, managerial ability, corporate image, customer satisfaction.